A comparison of metabolomic changes in type-1 diabetic C57BL/6N mice originating from different sources - Seunghyun Lee; Jae-Hwan Kwak; Sou Hyun Kim; Jieun Yun; Joon-Yong Cho; Kilsoo Kim; Daeyeon Hwang; Young-Suk Jung (Laboratory Animal Research, 2018)
Abstract Animal models have been used to elucidate the pathophysiology of varying diseases and to provide insight into potential targets for therapeutic intervention. Although alternatives to animal testing have been proposed to help overcome potential drawbacks related to animal experiments and avoid ethical issues, their use remains vital for the testing of new drug candidates and to identify the most effective strategies for therapeutic intervention. Particularly, the study of metabolic diseases requires the use of animal models to monitor whole-body physiology. In line with this, the National Institute of Food and Drug Safety Evaluation (NIFDS) in Korea has established their own animal strains to help evaluate both efficacy and safety during new drug development. The objective of this study was to characterize the response of C57BL/6NKorl mice from the NIFDS compared with that of other mice originating from the USA and Japan in a chemical-induced diabetic condition. Multiple low-dose treatments with streptozotocin were used to generate a type-1 diabetic animal model which is closely linked to the known clinical pathology of this disease. There were no significantly different responses observed between the varying streptozotocin-induced type-1 diabetic models tested in this study. When comparing control and diabetic mice, increases in liver weight and disturbances in serum amino acids levels of diabetic mice were most remarkable. Although the relationship between type-1 diabetes and BCAA has not been elucidated in this study, the results, which reveal a characteristic increase in diabetic mice of all origins are considered worthy of further study.